Concerns-Based Reverse Engineering for Partial Software Architecture Visualization - Hind Alamin M; Hany H Ammar (Politeknik Negeri Padang, 2020)
Recently, reverse engineering (RE) is becoming one of the essential engineering trends for software evolution and maintenance. RE is used to support the process of analyzing and recapturing the design information in legacy systems or complex systems during the maintenance phase. The major problem stakeholders might face in understanding the architecture of existing software systems is that the knowledge of software architecture information is difficult to obtain because of the size of the system, and the existing architecture document often is missing or does not match the current implementation of the source code. Therefore, much more effort and time are needed from multiple stakeholders such as developers, maintainers and architects for obtaining and re-documenting and visualizing the architecture of a target system from its source code files. The current works is mainly focused on the developer viewpoint. In this paper, we present a RE methodology for visualizing architectural information for multiple stakeholders and viewpoints based on applying the RE process on specific parts of the source code. The process is driven by eliciting stakeholders’ concerns on specific architectural viewpoints to obtain and visualize architectural information related these concerns. Our contributions are three fold: 1- The RE methodology is based on the IEEE 1471 standard for architectural description and supports concerns of stakeholder including the end-user and maintainer; 2- It supports the visualization of a particular part of the target system by providing a visual model of the architectural representation which highlights the main components needed to execute specific functionality of the target system, 3- The methodology also uses architecture styles to organize the visual architecture information. We illustrate the methodology using a case study of a legacy web application system.